2013
DOI: 10.1021/nn402077v
|View full text |Cite
|
Sign up to set email alerts
|

Activated Graphene-Based Carbons as Supercapacitor Electrodes with Macro- and Mesopores

Abstract: Electric double layer capacitors (or supercapacitors) store charges through the physisorption of electrolyte ions onto porous carbon electrodes. The control over structure and morphology of carbon electrode materials is therefore an effective strategy to render them high surface area and efficient paths for ion diffusion. Here we demonstrate the fabrication of highly porous graphene-derived carbons with hierarchical pore structures in which mesopores are integrated into macroporous scaffolds. The macropores we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
485
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 804 publications
(498 citation statements)
references
References 33 publications
9
485
3
1
Order By: Relevance
“…The specific capacitances were measured separately by cyclic voltammetry (CV) in a potential window of 0-3 V at a scan rate of 0.01-0.1 V s -1 and by galvanostatic charge/discharge (GCD) at a current density of 1 A g -1 according to equations 2 and 3 in the supplementary materials (Kim et al 2013;You et al 2015). The impedance was measured by electrochemical impedance spectroscopy (EIS) between 100 kHz and 10 mHz with an AC amplitude of 10 mV and the data were calculated from Nyquist plots.…”
Section: Methodsmentioning
confidence: 99%
“…The specific capacitances were measured separately by cyclic voltammetry (CV) in a potential window of 0-3 V at a scan rate of 0.01-0.1 V s -1 and by galvanostatic charge/discharge (GCD) at a current density of 1 A g -1 according to equations 2 and 3 in the supplementary materials (Kim et al 2013;You et al 2015). The impedance was measured by electrochemical impedance spectroscopy (EIS) between 100 kHz and 10 mHz with an AC amplitude of 10 mV and the data were calculated from Nyquist plots.…”
Section: Methodsmentioning
confidence: 99%
“…For example, some researchers have applied small-amplitude techniques such as impedance spectroscopy [57][58][59][60][61][62][63][64][65][66][67][68][69][70], while others have applied large-amplitude techniques such as cyclic voltammetry [71][72][73][74][75][76][77]. A few pioneers have even performed computer simulations [78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: Introductionmentioning
confidence: 99%
“…By using the SWCNTs with 1-2-nm diameters, the laser-scribed graphene/SWCNT MSC was observed to exhibit the best electrochemical properties. Kim et al [113] demonstrated the fabrication of highly porous graphene-based carbons with mesopores and macropores via chemical activation treatment of graphenederived hollow carbon spheres. The macropores were generated by assembly of these hollow graphene-derived spheres, and the mesopores were attributed to the KOH activation process.…”
Section: Graphene/graphene Oxidementioning
confidence: 99%